E-Komik Berbasis STEAM Bermuatan Pendidikan Karakter pada Materi Fisika-Gelombang Bunyi untuk Siswa Usia 16-18 Tahun - Sari, Devi Prima; Yuberti, Yuberti; Saregar, Antomi (Mataram University, 2025)
Research on the development of E-Comics using the STEAM approach based on character education for the topic of sound waves for high school students in class XI aimed to determine the feasibility of E-Comics through expert validation and to find out the response of students to the attractiveness of E-Comics with the STEAM approach based on character education for the topic of sound waves for high school students in class XI. The research method used in this study is the ADDIE model. The subjects involved in the research include 3 media experts, 3 subject matter experts, and high school students in class XI from MAN 1 Bandar Lampung and SMA Negeri 8 Bandar Lampung. The experts evaluated the validity of the material and its relevance, while teachers and students assessed the attractiveness of the E-Comics developed by the researcher. Based on the research conducted, it was found that the feasibility of E-Comics with the STEAM approach based on character education was very high according to expert evaluation criteria. The percentages of validation from experts were 93% for material and 95% for media. Teachers gave a positive response of 95%, and students also gave a positive response to the attractiveness of E-Comics with the STEAM approach based on character education as a learning medium. The results of small group testing were 94%, and field testing were 95%. It can be concluded that E-Comics with the STEAM approach based on character education for the topic of sound waves for high school students in class XI is very feasible and attractive and received positive responses to be used as a learning medium.